Smart Sukuk Berbasis Blockchain Tinjauan Maqasid Syariah Al-Najjar - Dimyati, Dimyati; Rosyadi, Moh. Imron; Fageh, Achmad (Jurnal Ilmiah Ekonomi Islam, 2023)
The concept of Blockchain-based Smart Sukuk involves the use of Blockchain technology and smart contracts in the issuance and execution of Sukuk. Smart Sukuk and Blockchain: One of the innovations of Blockchain systems is smart sukuk. Effective issuance of smart sukuk allows small and medium enterprises (MSMEs) to take advantage of it. Because it increases transparency and eliminates the possibility of fraud or speculation in sukuk transactions, Blockchain is a technology that builds trust between issuers and investors. Smart Contracts: Smart contracts run on the Ethereum Blockchain and allow smart sukuk to be automated and executed digitally. Smart contracts eliminate some of the components and parties involved in conventional sukuk, such as trustees, registrars, payment agents, calculation agents, arrangers, listing agents, transfer agents, and security depository. MSME Financing Potential: Blockchain-based Smart Sukuk has the potential to support the development of MSMEs and the deepening of the Islamic financial sector. Efficiency and Transparency: The use of Blockchain technology in Smart Sukuk can increase efficiency, transparency, and cost, allowing companies to utilize sukuk structures more efficiently